Job Characteristics on Employee Performance: Well-Being as Mediation and Inclusive Leadership as Moderation - Rini Juni Astuti; Bielsa Toyra Albany (Universitas Muhammadiyah Malang, 2026)
This study examines the effect of job characteristics on employee performance, with well-being as a mediating mechanism and inclusive leadership as a moderating condition. A quantitative survey was conducted among employees of an oil and gas company in West Java, Indonesia, involving 133 respondents (n = 133). Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study assessed job characteristics (autonomy, task variety, task significance, task identity, feedback), well-being (physical, psychological, social relationships, environment), inclusive leadership (openness, availability, accessibility), and employee performance (job knowledge, judgment, quality of outputs, innovation, teamwork, leadership, goal setting). The findings reveal that job characteristics positively and significantly predict employee performance (β = 0.452; t = 5.247; p = 0.000) and well-being (β = 0.452; t = 6.416; p = 0.000). Well-being also shows a significant positive effect on employee performance (β = 0.367; t = 4.595; p = 0.017). Mediation analysis confirms that well-being significantly mediates the relationship between job characteristics and employee performance (t = 4.219; p = 0.001), indicating that meaningful, autonomous, and feedback-rich jobs enhance performance partly by improving employees’ well-being. Moderation testing further demonstrates that inclusive leadership strengthens the job characteristics–performance relationship (t = 2.209; p = 0.027), suggesting that leaders who are open, accessible, and supportive amplify the performance gains from well-designed jobs. The structural model shows strong explanatory power for employee performance (R² = 0.749) and moderate explanatory power for well-being (R² = 0.326). Theoretically, this study contributes by integrating a psychological pathway (well-being) and a boundary condition (inclusive leadership) into the job design–performance linkage. Practically, the results highlight the importance of optimizing job design, investing in workplace well-being initiatives, and developing inclusive leadership behaviors to sustain higher performance in complex task environments. Overall, the study underscores that aligning job characteristics with employee well-being and inclusive leadership is pivotal for improving employee performance.